The Historical Sources of Nationalism in the Contemporary China - Mohammad Hussaini, (Technium Social Sciences Journal, 2020)
Chinese nationalism begun to rise as the Cold War ended in 1989. During the first two decades of twenty first century, Chinese nationalism as strong force has impacted Chinese public opinions as well as government decisions to a large extent. In the eyes of Chinese political elites, nationalism is force for unity that can keep China together as the communism has lost its appeal. This study explores the historical factors which best explain the sources of nationalism in contemporary China. For this purpose, I utilize qualitative analysis of nationalist discourse and deeds to gauge nationalist sentiment among the contemporary Chinese people and its political elites. The evidence suggests that nationalism in contemporary China mainly comes from Chinese the perceived injustice and insults done to China when it was dismembered by the imperial powers in nineteenth and the first half of twentieth centuries, the provocative moves against the rising China, the Chinese government’s propaganda campaign and the economic miracle in recent years.